Occurrence and Characterization of mcr-1-Positive Escherichia coli Isolated From Food-Producing Animals in Poland, 2011–2016 - Zając, Magdalena; Sztromwasser, Paweł; Bortolaia, Valeria; Leekitcharoenphon, Pimlapas; Cavaco, Lina M.; Ziȩtek-Barszcz, Anna; Hendriksen, Rene S.; Wasyl, Dariusz (Frontiers in Microbiology, 2019)
The emergence of transferable colistin resistance (mcr genes) poses a threat to the effective use of polymyxins, which are last resort drugs to treat infections by multidrug- and carbapenem-resistant Gram-negative bacteria. The aims of the study were to investigate the occurrence of colistin resistance, to determine possible resistance mechanisms and then characterize the mcr-positive Escherichia coli. From the national and EU harmonized antimicrobial resistance monitoring programs, a total of 5,878 commensal E. coli from faecal samples of turkeys, chickens, pigs and cattle collected in 2011-2016 were screened by Minimum Inhibitory Concentration (MIC) determination for the presence of resistance to colistin (R) defined as R > 2 mg/L. Strains with MIC = 2mg/L isolated in 2014-2016 were also included. A total of 128 isolates selected were obtained, and most (66.3%) had colistin MIC of 2 mg/L. PCR revealed mcr-1 in 80 (62.5%) isolates recovered from 61 turkeys, 11 broilers, two laying hens, one pig and one bovine. No other mcr-type genes (including mcr-2 to -5) were detected. Whole-genome sequencing (WGS) of the mcr-1-positive isolates showed high diversity in the Multi-Locus Sequence Types (MLST) of E. coli, plasmid replicons, antimicrobial resistance and virulence genes. mcr-1.1 was generally detected on the same contig as IncX4 (76.3%) and IncHI2 (6.3%) replicons. One isolate harbored mcr-1.1 on the chromosome. Various extended-spectrum beta-lactamase (blaSHV-12, blaCTX-M-1, blaCTX-M-15, blaTEM-30, blaTEM-52, and blaTEM-135) and quinolone resistance genes (qnrS1, qnrB19 and chromosomal gyrA, parC and parE mutations) were present in the mcr-1.1-positive E. coli. A total of 49 sequence types (ST) were identified with ST354, ST359, ST48 and ST617 being the most common. One isolate, identified as ST189, belonged to atypical enteropathogenic E. coli. Our findings show that mcr-1.1 has widely spread in production animals in Poland, particularly in turkeys and appears to be transferable mainly by IncX4 and IncHI2 plasmids spread across diverse E. coli lineages. Interestingly, most of these mcr-1-positive E. coli would remain undetected using phenotypic methods with the current ECOFF. Rapid spread of mcr-1 among turkeys could predict possible appearance of the gene in the food chain in Poland and Europe likely to affect the consumers.